Frequency and impact of childhood sexual and physical abuse on people using IAPT services. (3rd June 2021) - Verbist, Irini Laura; Allsopp, Kate; Huey, Dale; Varese, Filippo
Abstract : Objectives: This study explored the prevalence of childhood sexual/physical abuse (CSA/CPA) as identified by practitioners in Improving Access to Psychological Therapies (IAPT) services and clarified differences in clients' characteristics with and without a history of CSA/CPA. Methods: A retrospective analysis of a large dataset comprised of IAPT routine data and data from a local service evaluation reporting on clients' presenting problems. Results: 14% of IAPT clients ( n  = 1, 315) were identified with a record of CSA/CPA. CSA/CPA history was associated with longer duration and earlier age of onset of condition(s), greater number of presenting problems and post‐traumatic stress disorder co‐occurrence, higher intensity treatment delivery, and lower recovery rates. Conclusions: CSA/CPA history appears as an important feature in a sizable minority of IAPT clients; further work is required to meet clients' trauma‐related needs. Practitioner points: A sizable minority of IAPT clients (14%) present with a history of CSA/CPA as recorded in clinical notes. CSA/CPA history is associated with more complex and enduring presentations in IAPT clients. The reported CSA/CPA frequency is likely to be underestimates of the actual prevalence and impact of adverse childhood experiences in IAPT clients. Trauma‐informed inquiry and trauma‐specific screening tools would help practitioners to meet clients' trauma‐related needs.